Challenges Faced By Partnership Governance In Regional Development Of Maluku Province - Jusuf Madubun; Hadijah Madubun (Jurnal Manajemen Pelayanan Publik, 2023)
The Maluku Provincial Government still faces various issues in achieving equitable regional development. The challenges are not only extraordinary events such as the Covid-19 pandemic, but also the main factors are the dissatisfactory regulation and policy frameworks and synergy between the national, provincial and city/district governments. This will certainly affect the collaboration efforts with partners, whether they are domestic, third-party, or international partners. Based on such realities, this research aims to identify the depiction of partnership governance in regional development in Maluku Province. The method used in this research is descriptive-exploratory of qualitative approach. The results reveal that collaborative governance in regional development in Maluku Province has not been properly implemented due to several factors, including: 1) the improper governance of regulation and policy frameworks for collaboration in Maluku Province, as evidenced by the absence of regulations at the regional level as an elaboration of laws and government regulations governing collaboration with partners; 2) the ineffectiveness of  institutional collaborations in Maluku Provincial Government; and 3) the improper implementation of collaboration, both with domestic and international partners in various sectors such as education, energy, and maritime. With efforts to improve and enhance collaborative governance, it is expected that the development in Maluku Province is moving for the better.